KEMAHIRAN MENYIMAK DALAM PROSES PEMBELAJARAN BAHASA ARAB - Muhammad Jabir (Hunafa: Jurnal Studia Islamika, 2010)
According to linguists, there are four  skills of language which must be mastered by leaners learners in learning a language, Arabic is no exception.  First listening  skill, second speaking skill, third   reading skill and  fourth writing skill. In this article, the author will  focus his discussion on  the first  skill, namely  listening  skill. The reason is that  without  good  listening  skill, there will be  a lot of  misunderstanding in communication among the language users.Kata Kunci:  Kemahiran, Menyimak, Pembelajaran, Bahasa Arab